Theorizing Fiction in Film Non/Fiction: Some Thoughts on Recent German Film Theory - Slugan, Mario (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2019)
Despite fiction film arguably being the privileged object of film theory the notion of “fiction” has been undertheorized by film scholars in general and those working in German in particular. Perhaps the most important exception to this trend has been Gertrud Koch and Christiane Voss’ (2009) edited volume on fiction on the intersection of philosophy, film, and media studies. This paper tackles two of the most notable film scholarly contributions to the volume – Koch’s and Vinzenz Hediger’s – and their attempts to define fiction in terms of medium properties as well as their efforts to articulate all photographic films as simultaneously fictional and nonfictional. In the first case, I demonstrate that medium underdetermines whether something is fictional or not. In the second, I argue that although fiction is a temporally unstable category, it is possible to distinguish between fiction and nonfiction at a given moment in time. I conclude with a call to applying Kendall L. Walton’s (1990) transmedial theory of fiction to film, by listing a number of its advantages over competing proposals and by emphasizing its suitability for investigating the change in films’ fictional status over time. Table of contents image from Un homme de têtes / Four Troublesome Heads (Georges Méliès, 1898, France).